Dynamic Effect of Rudder Rotary Response on Ship Manoeuvrability. Issue 1 (February 2021) - Xi, Chen; Yongshun, Wu; Zhi, Pan; Sujun, Yang; Fei, Wang
Abstract: Simulation mathematical model of maneuverability such as zig-zag and turning circle test under different rudder and speed is built and the rudder rotary response effect on ship maneuverability parameters is analyzed extensively. In the paper, MMG (maneuvering model group) model is adopted to set up the 3 degrees of freedom governing equations of ships, in which the rudder rotary response is approximated by the assumption of uniform rotary speed. A sea-going vessel of 10 thousand deadweight tonnages is selected as the numerical simulation target to investigate the rudder rotary response effect on ship maneuverability parameters, such as the zig-zag and turning circle test. Some meaningful conclusions are concluded through comparative analysis, the conclusions indicate that rudder rotary response has remarkable effect on ship maneuverability, and it is a significant factor which needs to be taken into consideration for actual ships.